Mental health-related, existential, and biological factors are associated with the desire to hasten death in Mexican cancer patients undergoing palliative care: A single-center study - Oscar Rodríguez-Mayoral; Edith Monreal-Carrillo; Irazú Contreras-Yáñez; Silvia Allende-Pérez; Evandro Agazzi; Virginia Pascual-Ramos (PLoS ONE, 2025)
Introduction The wish to hasten death (WTHD) is a clinically significant phenomenon that arises from complex suffering. It has been predominantly studied in Caucasian populations, emphasizing the importance of gaining more diverse cultural perspectives. This study explores the factors associated with the WTHD in Mexican cancer patients receiving palliative care from one academic center, with a specific focus on its connection to dignity.“. Patients and methods The study, a cross-sectional research conducted between October 12, 2023, and August 30, 2024, involved patients with confirmed cancer diagnoses who were attending a palliative care service. Patients had applied the Patient Dignity Inventory (PDI), Schedule of Attitudes Toward Hastened Death (SAHD), Brief Edinburgh Depression Scale (BEDS), EORTC QLQ-C15-PAL to assess health-related quality of life, Karnofsky Performance Status Scale (KPSS) to assess functional capacity, and the Edmonton Symptom Assessment System. A PDI score ≥55 indicated a fractured sense of dignity (DPD), while a SAHD score ≥1 indicated the WTHD. Factors associated with the WTHD were identified using multiple logistic regression analysis. The study was approved by the IRB. Results The study included 302 primarily middle-aged (54.5 [45–64]) females (225 [74.5%]), with 9 years of education. They reported high severity of well-being (7 [1–7]) and tiredness (3 [0–6]). Their median KPSS score showed independence (80 [70–80]), despite impacts across all EORTC QLQ-C15-PAL dimensions. DPD was noted in 110 patients (36.5%). The most frequent diagnoses were breast cancer (114 [38%]), lung cancer (33 [11%]), and gastrointestinal cancer (28 [9%]). The WTHD was found in 94 patients (31.1%). Factors significantly associated included tiredness score (OR: 1.147, 95% CI: 1.044–1.261, p = 0.004), BEDS score (1.181, 1.085–1.284, p ≤ 0.001) and a DPD (1.979, 1.038–3.772, p = 0.04). Conclusions The WTHD was found in one out of every three Mexican cancer patients receiving palliative care and was linked to biological-, mental health-, and existential-related factors.